2021
DOI: 10.1186/s12877-021-02299-3
|View full text |Cite
|
Sign up to set email alerts
|

Frailty increases the risk for developing urinary tract infection among 79,887 patients with diabetic mellitus and chronic kidney disease

Abstract: Background Patients with diabetic mellitus (DM) and chronic kidney disease (CKD) are at an increased risk of urinary tract infection (UTI) due to their altered immunological integrity. These patients are similarly prone to developing frailty, a state of cumulative health deficits involving multiple domains and leading to adverse outcomes. Whether frailty predisposes affected individuals to UTI among patients with DM and CKD remains unclear. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 50 publications
2
18
0
1
Order By: Relevance
“…Multiple studies have shown that diabetes increases the risk for UTI complications such as recurrent UTI, bacteremia, requiring hospitalization for UTI treatment, and 30-day mortality: (i) In elderly individuals with diabetes-associated chronic kidney disease (CKD; N = 79,887; mean age = 59.6 years), the presence of age-associated frailty was a significant risk factor of UTI and urosepsis [ 63 ]; (ii) in a study from Greece, diabetic individuals (DM = 19; no DM = 81; median age = 60 years) were more susceptible to recurrent UTI (defined as ≥3 UTI in one year) with an OR of 5.5 ( P = 0.006) [ 64 ]; (iii) in an Australian study (DM = 396; no DM = 2391; overall mean age = 37.1 years), diabetic individuals were more likely to be hospitalized for UTI treatment (OR calc = 2.8; P < 0.001) requiring ~1.5 days longer hospital stay ( P = 0.04) compared to nondiabetics [ 65 ]; (iv) in a matched control study from the US ( N = 179,580; mean age = 56 years), compared to nondiabetics, the UTI recurrence within three months of first diagnosis of T2DM was ~3-times ( P < 0.0001) more common [ 66 ]; (v) in a prospective study of hospitalized diabetic patients with advanced CKD (glomerular filtration rate< 30 ml/min; N = 88; mean age = 68 years), individuals with higher fasting glucose showed slower (> 9 days) renal recovery after an episode of UTI and ~ 3 times higher susceptibility to developing Gram negative bacteremia [ 67 ]; (vi) in a study of elderly Dutch individuals, compared to nondiabetic controls ( N = 718, median age = 64 years), diabetic individuals ( N = 140; median age = 73 years) were at higher risk of recurrent UTI (OR (adjusted for age and cardiovascular disease) = 2.2; P = 0.017, higher risk for bacteremia (OR = 1.2; P = 0.037), and higher risk of 30-day mortality (OR = 2.0; P = 0.007) [ 40 ]; (vii) in a retrospective study from Taiwan, diabetic patients with late-stage CKD (glomerular filtration rate ≤ 30 ml/min; N = 225; mean age = 63.5 years) had an increased risk of acute kidney injury following an episode of UTI [ 68 ]; (viii) in a cohort of Japanese patients requiring hospitalization for the treatment of bacteremia resulting from UTI ( N = 70; mean age = 68 years), 17.1% were diabetic [ 69 ]; (ix) compared to nondiabetic controls ( N = 81; mean age = 66 years), diabetic patients with E. coli UTI ( N = 190; mean age = 69 years) showed a 1.2-fold higher incidence of urosepsis [ 57 ]; (x) in a cohort of elderly hospitalized for UTI treatment ( N = 251, mean age = 65.3 years), DM significantly increased the risk for death (OR = 22.66; P < 0.01) in a 30-day period following hospitalization [ 70 ]; and (xi) in a cohort of Dutch women, compared to nondiabetic controls ( N = 6958; mean age = 51 years), diabetic subjects ( N = 340; mean age = 65.5 years) were at a higher risk of recurrent UTI (OR (adjusted for age) = 2.0; P < 0.001) [ 71 ]. In summary, it is evident from clinical data that diabetes significantly increased risk of UTI complications such as recurrent UTI, bacteremia, and for requiring hospitalization for UTI treatment, with an important caveat that in majority of studies examining association between DM and UTI complications, diabetic subjects are ≥60 years of age.…”
Section: Diabetes As a Risk Factor Of Uti Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that diabetes increases the risk for UTI complications such as recurrent UTI, bacteremia, requiring hospitalization for UTI treatment, and 30-day mortality: (i) In elderly individuals with diabetes-associated chronic kidney disease (CKD; N = 79,887; mean age = 59.6 years), the presence of age-associated frailty was a significant risk factor of UTI and urosepsis [ 63 ]; (ii) in a study from Greece, diabetic individuals (DM = 19; no DM = 81; median age = 60 years) were more susceptible to recurrent UTI (defined as ≥3 UTI in one year) with an OR of 5.5 ( P = 0.006) [ 64 ]; (iii) in an Australian study (DM = 396; no DM = 2391; overall mean age = 37.1 years), diabetic individuals were more likely to be hospitalized for UTI treatment (OR calc = 2.8; P < 0.001) requiring ~1.5 days longer hospital stay ( P = 0.04) compared to nondiabetics [ 65 ]; (iv) in a matched control study from the US ( N = 179,580; mean age = 56 years), compared to nondiabetics, the UTI recurrence within three months of first diagnosis of T2DM was ~3-times ( P < 0.0001) more common [ 66 ]; (v) in a prospective study of hospitalized diabetic patients with advanced CKD (glomerular filtration rate< 30 ml/min; N = 88; mean age = 68 years), individuals with higher fasting glucose showed slower (> 9 days) renal recovery after an episode of UTI and ~ 3 times higher susceptibility to developing Gram negative bacteremia [ 67 ]; (vi) in a study of elderly Dutch individuals, compared to nondiabetic controls ( N = 718, median age = 64 years), diabetic individuals ( N = 140; median age = 73 years) were at higher risk of recurrent UTI (OR (adjusted for age and cardiovascular disease) = 2.2; P = 0.017, higher risk for bacteremia (OR = 1.2; P = 0.037), and higher risk of 30-day mortality (OR = 2.0; P = 0.007) [ 40 ]; (vii) in a retrospective study from Taiwan, diabetic patients with late-stage CKD (glomerular filtration rate ≤ 30 ml/min; N = 225; mean age = 63.5 years) had an increased risk of acute kidney injury following an episode of UTI [ 68 ]; (viii) in a cohort of Japanese patients requiring hospitalization for the treatment of bacteremia resulting from UTI ( N = 70; mean age = 68 years), 17.1% were diabetic [ 69 ]; (ix) compared to nondiabetic controls ( N = 81; mean age = 66 years), diabetic patients with E. coli UTI ( N = 190; mean age = 69 years) showed a 1.2-fold higher incidence of urosepsis [ 57 ]; (x) in a cohort of elderly hospitalized for UTI treatment ( N = 251, mean age = 65.3 years), DM significantly increased the risk for death (OR = 22.66; P < 0.01) in a 30-day period following hospitalization [ 70 ]; and (xi) in a cohort of Dutch women, compared to nondiabetic controls ( N = 6958; mean age = 51 years), diabetic subjects ( N = 340; mean age = 65.5 years) were at a higher risk of recurrent UTI (OR (adjusted for age) = 2.0; P < 0.001) [ 71 ]. In summary, it is evident from clinical data that diabetes significantly increased risk of UTI complications such as recurrent UTI, bacteremia, and for requiring hospitalization for UTI treatment, with an important caveat that in majority of studies examining association between DM and UTI complications, diabetic subjects are ≥60 years of age.…”
Section: Diabetes As a Risk Factor Of Uti Complicationsmentioning
confidence: 99%
“…The results from such analyses reveal that both age and female sex increase the risk of UTI independent of DM, although diabetic women are at >3-fold increased risk of ASB and UTI in comparison to men as shown in Table 5 and that the magnitude of UTI risk is different at each age category [ 66 , 76 , 77 , 96 99 ]. Moreover, among diabetic individuals, old age and age-associated frailty increase UTI risk by ~2-fold and the need for hospitalization for the treatment of UTI by 1.45-fold [ 63 , 96 , 100 ].…”
Section: Sex and Age As Uti Risk Factors In Addition To Dmmentioning
confidence: 99%
“…Frailty has been linked to elevated COVID-19 mortality among LTCF residents, reflecting a combination of increased incidence of infection as well as more adverse consequences—the same combination that has been observed for other infectious diseases. [ 62 , 63 ] Individuals with severe frailty or cognitive deficiencies require extensive assistance with daily routines and hence greater exposure if a staff person becomes infected. Moreover, frailty has a strong association with immune dysregulation that is likely to exacerbate vulnerability to COVID-19 as with other infectious diseases.…”
Section: Frailty and Comorbiditiesmentioning
confidence: 99%
“…Lodderomyces and Trichoderma are widespread fungi occurring in nature and are potential opportunistic pathogens associated with in ammation and infection in immunocompromised hosts [37,38]. Moreover, frail individuals are at a higher risk of developing urinary tract infections due to an immunocompromised status [39], and infectious arthritis compared to younger adults [40,41]. Brevibacterium and Aerococcus are common pathogens in urinary tract infections [42], of which Aerococcus is also a common pathogen causing joint infections [43].…”
Section: Relationship Indoor Microbiota Andmentioning
confidence: 99%